Creative Thinking Ability in Habits of Mind-based Ethnomathematics JUCAMA Learning Models - Heriyanto, Heriyanto; Zaenuri, Zaenuri; Walid, Walid (Universitas Negeri Semarang, 2021)
The Problem Submission and Solving (JUCAMA) learning model is a learning model that is oriented towards problem submission and solving to improve students' creative thinking skills.The purpose of this study is to determine the effectiveness of ethnomathematics JUCAMA learning models and to determine the influence of the mathematical habits of mind on the creative thinking ability of students. The research method used for this research is a mixed-method using a sequential explanatory design. The population in this study were students of class VIII in Junior High School of State at Sub-District Donggo Regency of Bima which is not a One-stop Middle School and the sample is class VIII of Junior High School of State 3 Donggo. Class VIII/A is the control class and class VIII/B is the experimental class. The results was showed that the average creative thinking ability of students taught by using etnomathematics JUCAMA learning model more higher than the average thinking ability of students taught by problem-based learning. Students who are taught with the ethnomathematical JUCAMA learning model experience an increase in creative thinking skills in the medium category, while students who are taught with problem-solving learning models experience an increase in creative thinking skills in the low category based on the N-gain category. In improving the creative thinking ability, the ethnomathematics JUCAMA learning models were applied to the experimental class more effective than problem-solving learning models were applied to the control class. There is the influence of the mathematical habits of mind on the creative thinking ability of students.